Genotype distribution of cervical human papillomavirus DNA in women with cervical lesions in Bioko, Equatorial Guinea - Carro-Campos Patricia; Piernas-Morales Ma Concepción; Silva-Sánchez Luís; Rueda Sonsoles; Nieto-Bona Ma Paz; García-Espinosa Benjamín; Cortés-Lambea Luís; Moro-Rodríguez Ernesto (BMC, 2009)
Abstract Background The HVP vaccine is a useful tool for preventing cervical cancer. The purpose of this study is to determine the most frequent HPV genotypes in Equatorial Guinea in order to develop future vaccination strategies to apply in this country. Methods A campaign against cervical cancer was carried out in the area on a total of 1,680 women. 26 of the women, following cytological screening, were treated surgically with a loop electrosurgical excision procedure (LEEP). Cases were studied histologically and were genotyped from paraffin blocks by applying a commercial kit that recognized 35 HPV types. Results Cytological diagnoses included 17 HSIL, 1 LSIL, 5 ASC-H and 3 AGUS. Histological diagnosis resulted in 3 cases of microinvasive squamous cell carcinoma stage IA of FIGO, 9 CIN-3, 8 CIN-2, 2 CIN-1, 3 flat condylomas and mild dysplasia of the endocervical epithelium. Fifteen of twenty-five cases genotyped were positive for HPV (60%). HPV 16 and 33 were identified in four cases each, HPV 58 in two other cases, and HPV 18, 31, 52, and 82 in one case, with one HPV 16 and 58 coinfection. Conclusion The frequency of HPV types in the African area varies in comparison to other regions, particularly in Europe and USA. Vaccination against the five most common HPV types (16, 33, 58, 18, and 31) should be considered in the geographic region of West Africa and specifically in Equatorial Guinea.